Zooplankton community dynamics in the N. Aegean front (E. Mediterranean) in the winter spring period - SIOKOU, I.; FRANGOULIS, C.; GRIGORATOU Μ.; PANTAZI, M. (Mediterranean Marine Science, 2014)
Zooplankton community composition was studied in the North Aegean frontal area in the winter-spring period along a trophic gradient going from the less saline and cold modified Black Sea water to the high salinity and temperature waters of Levantine origin. Samples were collected at the upper 100 m of three stations positioned along this gradient by using three nets with different mesh sizes (45 μm, 200 μm and 500 μm). Τhe community composition (all sizes) was differentiated along the gradient with smoother seasonal succession and higher diversity with increasing oligotrophy and salinity. The temporal variability of the community composition revealed significant changes in the January-April period as well as gradual decrease of diversity index values at the station positioned within the front. The major characteristic at this station was the abrupt increment and dominance of Centropages typicus in April, especially within the layer occupied by the modified Black Sea water. Significant difference in the community composition between March and April was a common feature in the whole study area and for all zooplankton fractions, though not of the same strength. The inflow of the Black Sea water and the trophic gradient were found to be important factors for the observed temporal variability and its spatial differentiation, while changes in the phytoplankton and protozoa abundance and community composition could account for the seasonal succession in species dominance.